A Linguistic Approach to Revelation 19:11-20:6 and the Millennium Binding of Satan - Kurschner, Alan E. (Linguistic Biblical Studies, 2022)
Is the establishment of the millennium binding of Satan cohesively linked with Jesus's victorious battle in the Book of Revelation? This study is the first to answer this frequently debated question from a linguistic perspective.